Role of sentinel lymph node biopsy in assessing the cancer spread to axilla in early breast cancer - Gumber, Ashutosh; Mudgal, Manish (International Surgery Journal, 2016)
Background:Sentinel lymph node (SLN) biopsy is a minimally invasive alternative to axillary lymph node dissection as a way to stage breast cancer in clinically node-negative patients. Objective of the study was to determine the safety and reliability of sentinel lymph node biopsy without axillary lymph node dissection (ALND) in early breast cancer patients. Methods: This prospective study was conducted in patients with operable breast cancer in a single surgical unit of our hospital. Patients with T1-T3 breast cancer with clinically negative axilla and patients with previous lumpectomy were included. All the patients had undergone complete axillary lymph node dissection after sentinel lymph node biopsy. All the specimens were sent separately for paraffin section histopathology. Results:Mean age of 35 female patients included was 54 years. SLN was identified in 94.29% cases and it could not be identified in 2 cases. SLN (96.97%) was most commonly identified at level I. Mean numbers of sentinel node and axillary node were 1.52 and 16.11 respectively. Study of SLN biopsy with methylene blue dye for staging the axilla was done with 81.25% sensitivity and 100% specificity. Positive predictive value was 100% and was able to negatively predict the axilla in 86.36% with an overall accuracy of staging of 96.97% and false negative rate of 18.75%. Conclusions:Sentinel lymph node biopsy without axillary lymph node dissection in sentinel lymph node negative breast cancers appears to be a safe and reliable procedure for determining the nodal status and ensuring the loco-regional control.